2019
DOI: 10.1002/adom.201901305
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Electromagnetic Field Enhancements through Suspended Metal/Dielectric/Metal Nanostructures and Plastic Phthalates Detection in Child Urine

Abstract: Plasmonic nanostructures exhibit intriguing optical properties due to spectrally selective plasmon resonance and thus have broad applications, including biochemical sensing and photoelectric detections. However, excited plasmons are often strongly influenced by the substrates supporting the metallic nanostructures, which not only weakens the intrinsic plasmon coupling effect, but also results in a great reduction of optical near‐field enhancement. Here, a plasmonic nanostructure combining collapsible Au‐nanofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The dye solution was initially coated uniformly over the entire surface. Since the hotspot is a saddle area of the structure, the capillary force drove the liquid to stay around the contact points of collapsed fingers as the ethanol vaporized. ,,, The fluorescent Nile blue molecules were easily trapped on the bottom of the saddle area at the contact/touching point, which is the hottest plasmonic hotspot exhibiting ultrastrong EM field enhancement.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dye solution was initially coated uniformly over the entire surface. Since the hotspot is a saddle area of the structure, the capillary force drove the liquid to stay around the contact points of collapsed fingers as the ethanol vaporized. ,,, The fluorescent Nile blue molecules were easily trapped on the bottom of the saddle area at the contact/touching point, which is the hottest plasmonic hotspot exhibiting ultrastrong EM field enhancement.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that ultrastrong EM fields can be realized between pairs of plasmonic nanostructures, which are formed by metallic nanoparticles with sub-nanometer interparticle gaps. Here, precise control of the physical gap at the sub-nanometer scale is critical to form strong and stable plasmonic hotspots. On the other hand, fluorescence quenching in the molecular emission process has been demonstrated at sub-5 nm scales. , Two main factors pose serious obstacles to understanding the mechanisms leading to fluorescence quenching experimentally.…”
mentioning
confidence: 99%
“…As a highly active SERS substrate, the label‐free detection of low‐concentration harmful plastic phthalates in a child's urine without any pretreatment was demonstrated by Hu et al. [ 121 ] According to the authors, their results suggest that this method is suitable for medical prediagnosis. Hu et al [ 121 ] reported the design of a device capable of a dual‐electromagnetic field enhancement.…”
Section: Micro‐ and Nanoplastics Detection Using Raman And Sersmentioning
confidence: 99%
“…[ 121 ] According to the authors, their results suggest that this method is suitable for medical prediagnosis. Hu et al [ 121 ] reported the design of a device capable of a dual‐electromagnetic field enhancement. It consists of a set of collapsible Au nanofingers on flexible polymer support.…”
Section: Micro‐ and Nanoplastics Detection Using Raman And Sersmentioning
confidence: 99%
“…The precise control of nanogaps between plasmonic nanoparticles (NPs) at a nanometer scale is crucial to produce a high density of strong and stable EM hot spots. To maintain the specific sub-nanometer gap, a dielectric layer can be considered as a nanogap spacer between two layered plasmonic metal nanostructures-namely, metal-dielectric-metal hybrid nano-architectures [27][28][29][30]. The dielectric spacer offers several benefits: protecting the plasmonic core from oxidation, tunning the LSPR properties, and maintaining a sub-nanometer gap between metal nanostructures to obtain a strong EM hotspot [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%